Chapter 4.9 A chorus of dancing voices curated by Katye Coe - Coe, Katye (Taylor & Francis, 2024)
I extended an invitation to a handful of dancer performer folk that I have been inspired by/ disarmed by/ learned from. Each of their responses came in the form of a 'prayer, spell, incantation, or wish'. I have curated them here as a chorus of dancing voices.